High Sensitivity of Non‐Fullerene Organic Solar Cells Morphology and Performance to a Processing Additive. Issue 23 (12th May 2022) - Alqahtani, Obaid; Lv, Jie; Xu, Tongle; Murcia, Victor; Ferron, Thomas; McAfee, Terry; Grabner, Devin; Duan, Tainan; Collins, Brian A.
Abstract: Although solvent additives are used to optimize device performance in many novel non‐fullerene acceptor (NFA) organic solar cells (OSCs), the effect of processing additives on OSC structures and functionalities can be difficult to predict. Here, two polymer‐NFA OSCs with highly sensitive device performance and morphology to the most prevalent solvent additive chloronaphthalene (CN) are presented. Devices with 1% CN additive are found to nearly double device efficiencies to 10%. However, additive concentrations even slightly above optimum significantly hinder device performance due to formation of undesirable morphologies. A comprehensive analysis of device nanostructure shows that CN is critical to increasing crystallinity and optimizing phase separation up to the optimal concentration for suppressing charge recombination and maximizing performance. Here, domain purity and crystallinity are highly correlated with photocurrent and fill factors. However, this effect is in competition with uncontrolled crystallization of NFAs that occur at CN concentrations slightly above optimal. This study highlights how slight variations of solvent additives can impart detrimental effects to morphology and device performance of NFA OSCs. Therefore, successful scale‐up processing of NFA‐based OSCs will require extreme formulation control, a tuned NFA structure that resists runaway crystallization, or alternative methods such as additive‐free fabrication. Abstract : Solvent additives are commonly used to optimize non‐fullerene acceptor (NFA) organic solar cells (OSCs). However, additive compatibility with OSC scale‐up remains questionable. This study finds that performance and morphology of NFA OSCs are extremely sensitive to extra residuals of additive due to a high sensitivity of NFA molecules to over‐crystallization, which can be affected by backbone halogenation.